2001
DOI: 10.1006/viro.2001.0952
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual Oligosaccharide Chains in Antigenic Properties, Intracellular Transport, and Biological Activities of Influenza C Virus Hemagglutinin-Esterase Protein

Abstract: The hemagglutinin-esterase (HE) glycoprotein of influenza C virus is composed of three domains: a stem domain active in membrane fusion (F), an acetylesterase domain (E), and a receptor-binding domain (R). The protein contains eight N-linked glycosylation sites, four (positions 26, 395, 552, and 603) in the F domain, three (positions 61, 131, and 144) in the E domain, and one (position 189) in the R domain. Here, we investigated the role of the individual oligosaccharide chains in antigenic properties, intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It has been shown that in other myxoviruses, N glycosylation of the F domain in Sendai and influenza C viruses is important for protein fusion activity. The absence of N glycosylation decreases the transport from the endoplasmic reticulum to the cytoplasmic membrane and alters protein trimerization (70,71,74). A glycosylated form of fusion protein has been reported (50 kDa) (4,19) with an approximate mass difference of 2 kDa compared to its immature isoform.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in other myxoviruses, N glycosylation of the F domain in Sendai and influenza C viruses is important for protein fusion activity. The absence of N glycosylation decreases the transport from the endoplasmic reticulum to the cytoplasmic membrane and alters protein trimerization (70,71,74). A glycosylated form of fusion protein has been reported (50 kDa) (4,19) with an approximate mass difference of 2 kDa compared to its immature isoform.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the mechanism by which temperature influences events involving HEF cell surface expression, we examined HEF oligomerization by using sucrose velocity sedimentation, as previously described (16). HEF expression plasmid-transfected COS-1 cells were cultured at 37°C for 24 h, followed by either further incubation at 37°C or a temperature shift to 33°C.…”
mentioning
confidence: 99%
“…N-linked glycosylation is an important post-translation modification that profoundly affects protein folding, oligomerization, and stability (Mitra et al, 2006). In addition, it is involved in trafficking modifications, ligand interactions (Meng et al, 2008), and enzyme activity (Hausmann et al, 1997;Sugahara et al, 2001). Because the potential N-linked glycosylation of UL2 occurs near the predicted beta-strand and within a potential strongly hydrophobic region, it might be associated with UDG activity.…”
Section: Discussionmentioning
confidence: 99%